2013
DOI: 10.1093/rfs/hht010
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Life Cycle Portfolio Choice with Housing Market Cycles

Abstract: During the last decades households in the U.S. have experienced that residential house prices move in a persistent manner, i.e. that returns are positively serially correlated. Since an owner-occupied home is usually the largest investment of a household it is important to understand how households act when they base their consumption and investment decisions on this experience. We show in a setting with housing market cycles and households who can decide whether they rent or own the home, that-besides the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…This finding fits the general pattern of preservation of housing wealth noted by Bradbury (2008Bradbury ( , 2010 and Cho and Sane (2013). We do observe several cases in 2006-2010 where households reduce housing equity and increase financial assets, consistent with Fischer and Stamos's (2013) observation that home ownership rates follow the house price cycle, but the reverse also happens in a few instances. Overall, even the poorest home-owning households maintain equity in principal residence when financial wealth is running out.…”
Section: (Iv) Prevalence and Determinants Of Low Wealthsupporting
confidence: 90%
“…This finding fits the general pattern of preservation of housing wealth noted by Bradbury (2008Bradbury ( , 2010 and Cho and Sane (2013). We do observe several cases in 2006-2010 where households reduce housing equity and increase financial assets, consistent with Fischer and Stamos's (2013) observation that home ownership rates follow the house price cycle, but the reverse also happens in a few instances. Overall, even the poorest home-owning households maintain equity in principal residence when financial wealth is running out.…”
Section: (Iv) Prevalence and Determinants Of Low Wealthsupporting
confidence: 90%
“…Nonrecurring costs occur when households move to owner-occupied homes. As in Bajari et al (2013), Fischer and Stamos (2013), and Van Hemert (2010), a household acquiring a new home faces a transaction cost of τQ t H t , in which Q t is the size of the new home. Transaction costs are also incurred if the household continues to be a homeowner but changes home size.…”
Section: The Modelmentioning
confidence: 93%
“…The rental yield of 2.5 percent implies that the price‐to‐rent ratio is 40; the estimate is 64 (Global Property Guide, 2014). We assume the rental yield is a constant portion of house price, but the empirical evidence has shown that the yield is time varying (Campbell et al, ) despite the impacts to both perishable and housing consumptions being small (Fischer and Stamos, ).…”
Section: Numerical Analysismentioning
confidence: 99%